EFFECT OF GIVING TAPE ON POWER JAVA (Ipomoea batatas) ON CONSUMPTION, ADDITIONAL WEIGHT AND BRAILER CHICKEN CONVERSION CONVERSION - Permata Ika Hidayati . (Fakultas Peternakan, Universitas PGRI Kanjuruhan Malang, 2016)
ABSTRACT The research was conducted on 16 March - 16 April 2016 at the Faculty of Animal Husbandry Field Laboratory Kanjuruhan Malang. The purpose of this study to determine the effect of giving the yeast tape on sweet potato flour to consumption, body weight gain and feed conversion of broiler. The material used is a broiler chicken cobb strain produced by PT. Patriot as many as 100 birds, starch sweet potato ( Ipomoea batatas ) as a prebiotic, probiotic yeast tape as bacteria Sacharomyces cerevisiae and commercial feed. The method used is a field experiment that starts from the preparation of materials research, preparation of the enclosure, the equipment used as well to the maintenance process. The parameters were observed in the form of performance consists of consumption, body weight gain and feed conversion of broiler. Data were analyzed using completely randomized design ( CRD ) factorial 2 x 3, if there is a real effect will be examined further by Duncan range test. The results of the study giving the combination of sweet potato flour ( Ipomoea batatas ) with yeast as synbiotic, not had a significant effect on consumption, body weight gain and feed conversion of broilers ( P > 0.05 ). At the level of 3% of sweet potato flour and 1.5 % yeast yellow tape is the best level to the average consumption of 1685.00 g, 968.27 g body weight gain and feed conversion of 1.75. The more probiotic should be partly offset by the provision of prebiotics. The conclusion of this experiment, administration of probiotics and prebiotics as feed synbiotic, no significant. Keywords : Sweet potato , yeast tape , the performance of broiler chickens.